Securing the Male Breadwinner: A Feminist Interpretation of PC 1003 - Forrest, Anne (Relations industrielles / Industrial Relations, 1997)
First, the author argues that labour's rights have been effectively the rights of working-class men because only men were constructed as family breadwinners for whom collective bargaining was both necessary and legitimate. Working-class women, by contrast, were defined as "non-working" wives and mothers, so had no claim to steady jobs at good wages or to union representation in their own right. Secondly, PC 1003 accorded rights to men (but not women) inasmuch as it codified an "industrial model" of workers' rights. Thirdly, PC 1003 supported and encouraged the growth of a "male model" of collective bargaining. Finally, the author briefly discusses the implications of a gendered analysis of PC 1003 for the study of industrial relations.